Molecular and morphological evidence of sibling species in Anopheles baileyi Edwards (Diptera: Culicidae) in Bhutan and Thailand - Pradya Somboon (2020)
© 2020 Elsevier B.V. This paper reports the results of a molecular and morphological study of Anopheles baileyi in Bhutan and Thailand. Phylogenetic analyses of ribosomal (ITS2) and mitochondrial DNA (COI) sequences revealed the presence of four genetically distinct clades, three in Bhutan (Clades I, II and III) and one in Thailand (Clade IV). Most of the larvae in the Bhutanese clades differed from those in the Thai clade in having seta 4-C branched, whereas it is single in the latter. The adults of each clade showed variation of wing markings and overlapping characters. The combination of characteristics of thoracic setae 1,2-P and abdominal seta 3-I was found to be useful for distinguishing the larvae. Pupae were inseparable. We provisionally recognize mosquitoes of Clades I, II, III and IV as members of a sibling species complex, the Baileyi Complex, denoted as species A, B, C and D, respectively. Species A is most likely the type form of An. baileyi s.s. because it was found adjacent to the type locality (Yatung, Tibet), and the others are unrecognized species.